2012
DOI: 10.1007/s00784-012-0880-4
|View full text |Cite
|
Sign up to set email alerts
|

Dental risk factors for osteonecrosis of the jaws: a CONDOR case–control study

Abstract: Background Reports of osteonecrosis of the jaw (ONJ) have associated this lesion to treatment with bisphosphonates (BPs) and dental procedures. In this study, we investigated the association of specific dental diagnoses and procedures with ONJ among patients with past BP use. Methods Dentists from three Practice-Based Research Networks provided ONJ cases and controls (1:3). Data gathered from patients and dental offices with two respective standard questionnaires included demographic, medical, pharmaceutical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
114
2
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(123 citation statements)
references
References 25 publications
5
114
2
2
Order By: Relevance
“…The drug dose and the cumulative dose play a role in the initiation of necrosis, as well as the specific type of BP used [4]. Even if the longer-term use of oral BPs should have a dose equivalence effect [48], it is notable that the mean time of presentation was approximately 3 yrs (38 months) in the patients in this study, as already described in the literature [12,16,35].…”
Section: Discussionsupporting
confidence: 59%
“…The drug dose and the cumulative dose play a role in the initiation of necrosis, as well as the specific type of BP used [4]. Even if the longer-term use of oral BPs should have a dose equivalence effect [48], it is notable that the mean time of presentation was approximately 3 yrs (38 months) in the patients in this study, as already described in the literature [12,16,35].…”
Section: Discussionsupporting
confidence: 59%
“…gingiva or palatal tissue, is composed of stratified epithelium and thin connective tissue; furthermore, it is considered to be one of the most protective tissue barriers against physical and chemical damage, bacterial infection, and environmental stress (14). Case control studies of patients with ONJ have indicated an increased risk of developing this condition with tooth extraction or the use of ill-fitting removable dental prostheses (15,16). These "event-related" oral conditions among BPtreated patients can lead to inflammation in the oral mucosa tissue that likely activates oral barrier immunity.…”
Section: Osteonecrosis Of the Jaw (Onj)mentioning
confidence: 99%
“…Finally, eight studies met the inclusion criteria. The eight included studies were comprised of 1,389 cases and 569,620 controls [4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Of the included studies, two were case-control studies, and the remaining six were cohort studies.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%